Anti-inflammatory and Oto-Protective Effect of the Small Heat Shock Protein Alpha B-Crystallin (HspB5) in Experimental Pneumococcal Meningitis - Erni, Silvia T.; Fernandes, Gabriella; Buri, Michelle; Perny, Michael; Rutten, Rolf Jan; van Noort, Johannes M.; Senn, Pascal; Grandgirard, Denis; Roccio, Marta; Leib, Stephen L. (Frontiers in Neurology, 2019)
Sensorineural hearing loss is the most common long-term deficit after pneumococcal meningitis (PM), occurring in up to 30% of surviving patients. The infection and the following overshooting inflammatory host response damage the vulnerable sensory cells of the inner ear, resulting in loss of hair cells and spiral ganglion neurons, ultimately leading to elevated hearing thresholds. Here, we tested the oto-protective properties of the small heat shock protein alpha B-crystallin (HspB5) with previously reported anti-inflammatory, anti-apoptotic and neuroprotective functions, in an experimental model of PM-induced hearing loss. We analyzed the effect of local and systemic delivery of HspB5 in an infant rat model of PM, as well as ex vivo, using whole mount cultures. Cytokine secretion profile, hearing thresholds and inner ear damage were assessed at predefined stages of the disease up to 1 month after infection. PM was accompanied by elevated pro-inflammatory cytokine concentrations in the cerebrospinal fluid (CSF), leukocyte and neutrophil infiltration in the perilymphatic spaces of the cochlea with neutrophils extracellular trap formation during the acute phase of the disease. Elevated hearing thresholds were measured after recovery from meningitis. Intracisternal but not intraperitoneal administration of HspB5 significantly reduced the levels of TNF-α, IL-6 IFN-γ and IL-10 in the acute phase of the disease. This resulted in a greater outer hair cell survival, as well as improved hearing thresholds at later stages. These results suggest that high local concentrations of HspB5 are needed to prevent inner ear damage in acute PM. HspB5 represents a promising therapeutic option to improve the auditory outcome and counteract hearing loss after PM.